Oxidative Molecular Layer Deposition Tailoring Eco-Mimetic Nanoarchitecture to Manipulate Electromagnetic Attenuation and Self-Powered Energy Conversion - Jin-Cheng Shu; Yan-Lan Zhang; Yong Qin; Mao-Sheng Cao (Nano-Micro Letters, 2023)
Highlights Drawing wisdom and inspiration from nature, an eco-mimetic nanoarchitecture is constructed, featuring tunable electromagnetic properties and high-efficiency energy attenuation. Through in-depth insight into the microstructure, the material basis of electromagnetic response is clearly revealed to establish an intrinsic connection between microscopic electronic structure and macroscopic electromagnetic properties. A creative self-powered energy conversion device is constructed, with the integrated functions including electromagnetic protection and waste energy recycling, which offers a new horizon for the fields of energy and environment.